Analysis of Factors Affecting the Success of Sociocultural Education Approach in Preventing Tuberculosis in Tapanuli Selatan Regency - Edy Sujoko; Anto J. Hadi; Dewani Harahap; Matius Rantesalu; Edwinn Sallipadang; Farida Utaminingtyas; Juni Andriani Rangkuti; Asdi Lastari (Journal of Public Health and Pharmacy)
Introduction: Tuberculosis is still becoming one of the deathliest infectious diseases in the entire world and has become the most urgent public health challenge globally. This study aims to analyze the factors affecting the success of the sociocultural education approach in preventing Tuberculosis in Tapanuli Selatan Regency.